Some Pyrimidine Derivatives as Corrosion Inhibitor for Mild Steel in Hydrochloric Acid - Ansari K.R.; Sudheer; Singh A.; Quraishi M.A. (My University, 2025)
The inhibition effect of four pyrimidine derivatives (PPDs) on the corrosion of mild steel in hydrochloric acid medium has been investigated using gravimetric measurements, electrochemical impedance spectroscopy, potentiodynamic polarization, and energy dispersive x-ray spectroscopy (EDX) techniques. Electrochemical impedance spectroscopy (EIS) data showed that the addition of PPDs increases the charge-transfer resistance (Rct) and decreases the double-layer capacitance (Cdl). Potentiodynamic polarization revealed that PPDs acted as mixed-type inhibitors but are predominantly cathodic. The adsorption of studied compounds obeyed the Langmuir's adsorption isotherm. EDX and quantum chemical calculations support the experimental results. © 2015, Copyright © Taylor & Francis Group, LLC.